Penerapan Metode Rhythmical Tapping Pada Kasus Latah : Studi Kasus Tunggal - Nining Lestari; Rahmita Andareza; Anggit Pambudi (22003) (Jurnal Terapi Wicara, 2024)
Latah is a fluency rhythm disorder where people who experience latah have the characteristic of repeating other people's speech or their speech. So that it prevents the message from being perfectly. people who experience fatigue feel embarrassed about their latitude so they often avoid interacting with other people and they are annoyed, tired, and anxious about their latitude. There is still little research on handling this talkativeness, which is the reason for carrying out this research.